Leader Behaviors On Organizational Change in Multinational Company - Nurillah Jamil Achmawati Novel; Yudo Anggoro; Marsha Aulia Hakim (Aliansi, 2022)
Change is a certainty that occurs in a dynamic organization. The role of the leader in mobilizing and managing people in the organization greatly influences adaptation to change. This study aims to assess the behavior of leaders in multinational companies that are undergoing massive organizational change. Qualitative and quantitative approaches are used to optimally explore supporting data in analyzing leader behavior in organizational change. They involved respondents and participants from all divisions in the company. The results show that all dimensions tested are in the "good" category. Meanwhile, the dimension with the highest score is "Inspirational Motivation," which is also supported by qualitative statements from the participants. Perubahan adalah suatu kepastian yang terjadi pada sebuah organisasi yang dinamis. Peran pemimpin dalam menggerakkan dan mengelola orang-orang dalam organisasi tersebut sangat mempengaruhi  adaptasi terhadap perubahan. Penelitian bertujuan untuk menilai perilaku pemimpin pada perusahaan multinasional yang sedang melakukan perubahan organisasi secara masif. Pendekatan kualititatif dan kuantitatif digunakan untuk menggali secara optimal data-data yang mendukung dalam analisis perilaku pemimpin pada perubahan organisasi ini. Melibatkan responden dan partisipan dari seluruh divisi di perusahaan. Hasilnya menunjukkan bahwa seluruh dimensi yang diuji pada kategori “baik”. Sedangkan dimensi dengan skor tertinggi adalah “Inspirational Motivation” yang didukung pula dengan pernyataan kualitatif para partisipan.